Leveraging Blockchain Technology to Create a More Resilient Supply Chain for Energy Industry - Kariri, Mousa (International Journal of Supply Chain Management, 2023)
Purpose: Blockchain is an evolving technology that has attracted considerable attention over the past few years from emerging businesses, energy supply enterprises, technology developers, financial institutions, government agencies, and academic institutions. Many references from these contexts describe blockchain as being capable of delivering substantial benefits and creativity. This paper aims to investigate the way in which blockchain technology is likely to inï¬‚uence future supply chain practices in energy sector. Methodology: A systematic review of both academic and nonacademic literature was conducted to gain a deep insight on the possibilities of leveraging the blockchain technology to create a more resilient supply chain for oil & gas industry. Toward this goal, the theoretical foundations of numerous research papers published in high-profile scientific journals over the past few years, along with several reports generated by well reputable and prestigious consulting firms that have been used to outlook the potential and relevance of blockchain technology for energy industry applications. Results: Blockchain can bring many opportunities to the oil & gas industry, such as reducing transaction costs and improving transparency and efficiency. However, since it is still in the early stage of the application, there are still many challenges, primarily technological, regulatory and system transformation. The development of blockchains in the oil & gas industry will move toward hybrid blockchain architecture, multi-technology combination, cross-chain, hybrid consensus mechanisms, and more interdisciplinary professionals. Unique Contribution to Theory, Practice and Policy: This paper offers valuable insight for supply chain practitioners into how blockchain technology has the potential to disrupt existing supply chain provisions as well as a number of challenges to its successful spreading. To the best of the author's knowledge, this paper is one of the first studies in the Kingdom of Saudi Arabia to explore the possibility of leveraging the blockchain technology to create a more resilient supply chain for oil & gas industry. Blockchain is a promising breakthrough technology and is highly applicable to vast businesses. However, it is still hard to find empirical evidence to show the comparison between blockchain approaches and traditional approaches. In view of this, businesses should realize that blockchain technology has not yet reached an optimal level of maturity, and therefore thorough feasibility studies should be conducted before using this technology.